Biodiverse coffee plantations provide co‐benefits without compromising yield - Dale R. Wright; Ascelin Gordon; Ruth E. Bennett; Matthew J. Selinske; Pia E. Lentini; Georgia E. Garrard; Amanda D. Rodewald; Sarah A. Bekessy (Journal of Sustainable Agriculture and Environment)
Abstract Introduction Coffee is a ubiquitous global commodity that is cultivated with a wide range of practices, each with different, yet poorly understood trade‐offs between management intensity, yield, and biodiversity. For example, monocultures prioritise coffee production, but do not necessarily deliver the highest coffee yields, nor the greatest profits. Understanding these trade‐offs is key to informing sustainable coffee production. Methods We synthesized the literature on these relationships, finding that agroforestry farming systems support greater biodiversity while often producing coffee yields that are comparable to monoculture systems. Results Over half of studies (57%) failed to detect a trade‐off between yield and biodiversity in agroforestry systems. Of the 16 cases that investigated pollinators and yield, 85% showed a positive relationship. Farm proximity to natural forests also improved both biodiversity outcomes and coffee yields. Conclusion Studies in our data set revealed that agroforestry systems can deliver additional ecosystem services including carbon sequestration and pest control, with economic benefits accrued through income diversification and improvements to coffee bean quality. Our results illustrate how agroforestry systems within the coffee sector can return positive socio‐ecological outcomes.